The determinants of quality and satisfaction in the opinion of small medical service enterprises’ customers – the chosen problems - Klimecka-Tatar, Dorota; Kowalik, Kamila (Journal of Education, Health and Sport, 2019)
The objective of the article is to identify the determinants of service quality and satisfaction in the opinion of small medical service enterprises’ customers. The first part contains literature review in the field of service quality and the satisfaction as its important factor. Afterwards, the results of empirical research have been presented. Anonymous survey was conducted among customers of small medical service enterprises. The questionnaire regarding the significance assessment of chosen determinants of satisfaction, which respondents made using Likert scale, indicated that particular factors influence the quality and satisfaction of medical service provided by small enterprises to a different extent.